miR-885-3p promotes hepatocellular carcinoma metastasis by targeting TASP1 to stabilize HIF-1α and activate hypoxia-driven angiogenic and invasive programs - Yunfeng Zhao; Haoxin Shen; Yibo Sun; Jinkun Song; Jing Bo; Shan Zheng; Chenguang Sun; Jinxiu Li; Hongyu Wang; Yinsen Song (Molecular Biology Reports, 2026)

Integrated electronic nose, GC–MS, and metagenomic analyses reveal volatile flavor and microbial community differences in heap-fermented grains of Jiangxiangxing Baijiu across different fermentation degrees - Guiyin Li; Lixia Shen; Lei Nie; Ping Tang; Qimuge Shan; Liqin Qin; Shuangxi Fan; Xuewu Guo (Food Research International, 2026)

Decoding lipid signatures and aroma characteristics of four Chinese traditional dark teas via integrative lipidomics, volatilomics, and quantitative descriptive analysis - Shan Zhang; Ruizhi Tang; Yunxia Wang; Ying Wang; Chuang Zhou; Rui Shen; Rui Liang; Niuniu Mao; Yinzi Chen; Nan Deng; Qinghua Zhou; Jia Li; et al. (Food Research International, 2026)

Membrane-regulated seawater electrolysis for sustainable hydrogen production - Zhongting Liu; Jingfen Yuan; Sunpeng Shan; Guangpu Li; Song Gu; Cheng Chen; Wei Yu; Mingzhu Zhou; Saleem Raza; Ying Liu; Hongjun Lin; Yang Jiao; et al. (Water Research, 2026)

The transcription factor AtANAC070 enhances zinc tolerance by promoting AtMTP1 expression in Arabidopsis thaliana - Jia Qi Li; Su Li; Chuan Jin Shan; Fang Wei Yu; Ren Fang Shen; Xiao Fang Zhu (Plant Cell Reports, 2026)

Corrigendum to: “Benzo[a]pyrene exposure promotes RIP1-mediated necroptotic death of osteocytes and the JNK/IL-18 pathway activation via generation of reactive oxygen species” [Toxicology, 476, June 2022, 153244] - Tao Zhang; Yuchen Shen; Ruirong Zhu; Weiyan Shan; Yurong Li; Ming Yan; Yun Zhang (Toxicology, 2026)

Intracranial EEG reveals working memory-related dynamics and connectivity in human white matter - Shen Zhang; Peng-Hu Wei; Longzhou Xu; Chao Zhang; Na Ao; Haoshu Xu; Yanfeng Yang; Lirou Tan; Zhilin Li; Yali Huang; Jin Li; Jing Liu; et al. (Science Bulletin, 2026)

From inhibition to degradation: advances in highly selective targeting strategies for HPK1 - Longbin Yu; Rui Yan; Yashi Li; Huijie Wu; Zhe-Shan Quan; Xiaoting Li; Qing-Kun Shen (Molecular Diversity, 2026)

Multilayer Validation Reveals a Glia-Associated Secretome Signature in Temporal Lobe Epilepsy - Yang Dai; Zesheng Li; Quanlei Liu; Xiaotong Fan; Chunhao Shen; Yumin Luo; Yongzhi Shan; Guoguang Zhao (Journal of Molecular Neuroscience, 2026)

Quantum chemical insights into radical-selective photolysis and toxicity evolution of carbamazepine - Yifan Shen; Yuming Yang; Haolin Liu; Guizhou Xu; Tao Shan; Yi Lu; Zongcheng Zhu; Wentao Li; Aimin Li (Journal of Water Process Engineering, 2026)

Molecular mechanisms underlying the maintenance of protein homeostasis in pearl gentian grouper under acute high-temperature stress - Qiu-Ting Yang; Ren-Xie Wu; Yan-Shan Liang; Ben-Ben Miao; Su-Fang Niu; Feng-Ling Lei; Fan-Li Long; Zhen-Bang Liang; Yu-Xin Shen; Yu Fu (Journal of Thermal Biology, 2026)

Observations of polycyclic aromatic hydrocarbons at Changbai Mountain in Northeast Asia: Characteristics, transboundary transport, and health impacts - Ye Shan; Yifan Li; Lanxin Zhang; An’an Qi; Yujiao Zhu; Yanbin Qi; Lingxiao Yang; Liubin Huang; Jiangshan Mu; Mingxuan Liu; Hongyong Li; Lingli Zhang; et al. (Journal of Environmental Sciences, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

In-situ sulfur element-induced heterogeneous interface engineering for high-performance supercapacitors - Mingzhe Shan; Yi Jiang; Ruixiang Xu; Bin Cai; Yi Gao; Heju Zhao; Jiaming Wang; Yaozeng Lu; Xiqing Song; Surong Tan; Yishan Yuan; Zining Li; et al. (Chemical Engineering Journal, 2026)

Highly RAGE-expressing macrophage membrane-derived nanovesicles as efficient AGEs scavengers for alleviating vascular complications of diabetes mellitus - Yi Sun; Junjie Shen; Jianyang Shan; Xiang Li; Bingbo Bao; Yunlong Yang; Xianyou Zheng (Chemical Engineering Journal, 2026)

Mechanisms of flavonoid-mediated amelioration of MASLD: flavonoids, their metabolites or impact on gut microbes? - Ruxuan Chen; Xionghui Wu; Ning Yin; Enjun Xie; Shumin Sun; Jie Shen; Yunmei Chen; Fenghua Zhou; Tao Li; Qili Li; Donglin Su; Fuhua Fu; et al. (Critical Reviews in Food Science and Nutrition, 2026)

Multi-omics analysis provides genetic evidence for the involvement of cell adhesion pathway in the pathogenesis of biliary atresia - Rui Dong; Jinhang Zhu; Chunjing Ye; Fenglong Sun; Cong Huai; Wei Zhou; Jiajie Zhu; Xiaoqi Feng; Qiange Xiao; Deqian Chen; Yifan Yang; Ran Yang; et al. (Science China Life Sciences, 2026)

Transforming bioresources for high-efficiency energy storage: Utilizing porous carbon derived from reed in supercapacitor applications - Shan Zhong; Shen Li; Longyun Dai; Xiaojun Zheng; Shuang Wang; Xin Zhao (Bioresource Technology, 2026)

The transcription factor BRN2 confers cadmium tolerance by regulating SAM1 expression in Arabidopsis - Su Li; Jing Huang; Jia Qi Li; Chuan Jin Shan; Ren Fang Shen; Da Li Zeng; Jin Chen; Xian Jiao Guan; Xiao Fang Zhu; Ting Wu Liu; Yong Gang Xu (Plant Science, 2026)

Age-related digestive capacity decline modulates the kinetic patterns of starch and protein digestion from varied diets: An in vitro study - Huilin Shen; Yimeng Shan; Dezhi Li; Kexin Li; Jing Wang; Yue Zhang; Yang Li; Li-Tao Tong (Food Research International, 2026)

Soil infiltration and slope stability of shrub-covered loess slopes on the northeastern Qinghai–Tibet Plateau: experimental and numerical simulation - Lingshan Wei; Shen Liang; Xiaoqing Shan; Dongzhu Duojie; Yabin Liu; Haili Zhu; Guorong Li; Xiasong Hu (Journal of Mountain Science, 2026)

Mechanisms of Weakening in Coal-Measure Rocks by Hyperalkaline Fluids - Shun Liang; Jinhang Shen; Derek Elsworth; Changhao Shan; Qiangling Yao; Qiang Wang; Zhaohui Chong; Xuehua Li (Rock Mechanics and Rock Engineering, 2026)

Short-term and long-term effects of outdoor artificial light at night on reproductive hormones among infertile women from a preconception cohort study - Wenbin Fang; Cun Huang; Ying Tang; Mengdie Li; Yaning Sun; Yanlan Tang; Yinyin Chen; Yawen Cao; Jiqi Fang; Kunjing He; Jing Shen; Zhiyuan Huang; et al. (International Journal of Biometeorology, 2026)

High-latitude species with temperature-dependent sex determination will face an elevated risk from climate change - Jun Zhong; Shan Li; Ming-Shen Hong; Mei-Lian Song; Han-Yi Lan; Xiang Ji (Biodiversity and Conservation, 2026)

Lignite-enhanced aerobic composting of acidified soybean soapstock by-products: reducing carbon and nitrogen loss and accelerating composting process - Denglun Chen; Shan Li; Shugang Zhang; Mingchuan Yang; Tianlin Shen; Yanpeng Zhang; Zekun Wang; Long Zhang; Songyuan Wang; Yuanyuan Yao; Guiwei Wang; Xiaoqi Wang; et al. (Waste Management, 2026)

Whole-genome resequencing unveils the phylogeographic coevolution of Oncomelania hupensis with Yangtze River dynamics in China - Lei Duan; Fang Luo; Qin Liu; Shen Chen; Xia Tian; Wen-Wen Lv; Lu He; Zi-Rui Ren; Jing Xu; Xiao-Nong Zhou; Shi-Zhu Li; Shan Lv; et al. (Molecular Phylogenetics and Evolution, 2025)

Interfacial Schottky junction-enhanced charge separation in BC/CoFe2O4/nZVI for photocatalytic removal of complex pollutants via peroxymonosulfate activation - Ye Yang; Shuang Liu; Maolei Li; Jiaxiang Li; Mihail-Simion Beldean-Galea; Hua Pan; Qingquan Xue; Shengdao Shan; Xiaofeng Shen (Chemical Engineering Journal, 2025)

The evolution of organic matter sources and sedimentary environments in lakes during the Eocene Climatic Optimum - Chuan Xu; Guangrong Peng; Pei Liu; Ye He; Peimeng Jia; Xuanlong Shan; Guoli Hao; Mengrong Shen; Kang Li (Marine and Petroleum Geology, 2025)

Effect of pulsed magnetic field on the rheological properties, structure, quality attributes of rice starch gel - Jing Wang; Yang Li; Huilin Shen; Jiaxin Li; Yimeng Shan; Mengzi Nie; Ning Li; Yue Zhang; Li-Tao Tong (Carbohydrate Polymers, 2025)

Impact of mycotoxins on placental function: Focus on cyclopiazonic acid, deoxynivalenol, patulin, and zearalenone's metabolites - Huiqian Zhang; Xiuwei Shen; Jiayi He; Qingyuan Wang; Yunbing Tang; Peipei Pan; Ren-Shan Ge; Xiaoheng Li (Chemico-Biological Interactions, 2025)

Strong coupling between the carbon and nitrogen cycles, environmental change, and organic carbon enrichment during the early–middle Eocene - Chuan Xu; Guangrong Peng; Pei Liu; Ye He; Peimeng Jia; Xuanlong Shan; Guoli Hao; Mengrong Shen; Kang Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Biofilm-enhanced PFAS removal in constructed wetlands: Sewage sludge biochar drives adsorption and microbial synergy - Fuhao Zhang; Cheng Shen; Yaqian Zhao; Lingwei Kong; Feng Ju; Bin Ji; Yu Bon Man; Shengdao Shan; Yuliang Li; Jin Zhang (Chemical Engineering Journal, 2025)

Nitrogen-oxygen radical generator-mediated in situ activation of live-cell prodrug for rational combination therapy - Ting Hou; Zi-Tao Shen; Wan-Ting Chen; Yang Song; Yin-Yu Yan; Zi-Jiang Luo; You-Yang Li; Yu-Ting Shan; Rui-Cheng Li; Tian-Yu Shen; Jia-Qin Long; Li Yin; et al. (Chemical Engineering Journal, 2025)

Emission of marine microbes via sea spray aerosol generation: Enrichment, influencing factors and the potential role in marine carbon cycle - Linyao Wu; Ting Liu; Yingyi Zhang; Yuhan Shen; Yinxi Yao; Zhaokang Ruan; Yee Jun Tham; Wei Song; Shan Huang; Jun Li; Senchao Lai (Atmospheric Environment, 2025)

Single-cell sequencing analysis and multiple machine learning methods identified immune-associated SERPINB1 and CPEB4 as novel biomarkers for COVID-19-induced ARDS - Hua Yang; Wenjing Wang; Junnan Huang; Yan Yan; Shan Wang; Qianran Shen; Jingjie Li; Tianbo Jin (The Science of Nature, 2025)

Vertical variations of ozone transport flux at multiple altitudes and identification of major transport direction in the North China Plain - Hanyu Zhang; Longyue Lv; Zhiliang Yao; Wantong Guo; Xuejun Wang; Wenxing Shan; Xin Li; Xianbao Shen (Journal of Environmental Sciences, 2025)

Front margin tectonic deformation characteristics of the Xu–Su arc tectonic belt and its tectonic implications - Rong-ying Zheng; Yun-sheng Yao; Jun Shen; Hao-yuan He; Chun-shan Guo; Xiao-hui Yu; Xun-ye Dai; Lu-wei Li; Xuan-kai Jiao; Zhong-yuan Yu; Zhi-tao Gao (Applied Geophysics, 2025)

The day-one experiment at SLEGS: systematic measurement of the ( γ , 1n) cross sections on 197 Au and 159 Tb for resolving existing data discrepancies - Zirui Hao; Gongtao Fan; Hongwei Wang; Longxiang Liu; Hanghua Xu; Yue Zhang; Yuxuan Yang; Sheng Jin; Kaijie Chen; Zhicai Li; Pu Jiao; Qiankun Sun; et al. (Science Bulletin, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Antithrombotic macrocyclic sesquiterpene pyridine alkaloids from Tripterygium hypoglaucum - Qiong Jin; Jia-Shan Shen; Xian-Run Wu; Hui-Zhen Peng; Zi-Hao Fu; Li-Qiang Chen; Yun-Li Zhao; Min Ye; Xiao-Dong Luo (Phytochemistry, 2025)

Harnessing the MYB51/SWEET20 module to increase soybean yield by facilitating sugar supply to sink organs - Jiafang Shen; Dong Cao; Songli Yuan; Qingnan Hao; Hongli Yang; Yi Huang; Lihong He; Jialing Yuan; Zhonglu Yang; Shuilian Chen; Zhihui Shan; Wei Guo; et al. (Plant Cell Reports, 2025)

Searching for neutrinoless double-beta decay of 136 Xe with PandaX-4T - Shu Zhang; Zihao Bo; Wei Chen; Xun Chen; Yunhua Chen; Zhaokan Cheng; Xiangyi Cui; Yingjie Fan; Deqing Fang; Zhixing Gao; Lisheng Geng; Karl Giboni; et al. (Science Bulletin, 2025)

Greenness, nighttime light, and couple fecundability: A national cohort study between 2014 and 2020 - Mengyao Li; Xinghou He; Bin Zhang; Hongbing Xu; Jianbin Wu; Xuyang Shan; Ya Zhang; Huiying Xu; Hongguang Zhang; Yuan He; Yan Fang; Zuoqi Peng; et al. (Environmental Research, 2025)

Synergistic effects of photothermal response and Schottky junction for enhanced photothermal-assisted photocatalytic hydrogen production - Pengnian Shan; Kun Geng; Li Guo; Liqiang Kuang; Yu Shen; Bo Xiong; Jianhua Hou; Feng Guo; Guangzhao Wang; Weilong Shi (Chemical Engineering Journal, 2025)

The dual-targeted transcription factor BAI1 orchestrates nuclear and plastid gene transcription in land plants - Jing Qin; Yelin Shan; Hao Liu; Zhangzhi Xue; Yike Xie; Guoxin Yuan; Yiming Zou; Xiaonuan Hao; Yunpeng Zhu; Xuan Shen; Meng Li; Xu Wang; et al. (Molecular Plant, 2025)

Equilibrium tendency of river channel adjustment in response to upstream damming: A case study of the Lower Yellow River - Yi Shen; Shan Zheng; Chao Qin; Jie Li; Zipu Ma; Baosheng Wu; Mengzhen Xu; Yuan Xue (Journal of Hydrology, 2025)

NAT10 primes a post-transcriptional repertoire essential for the maintenance of spermatogonial homeostasis - Xiaoli Zhu; Caoling Xu; Xue Jiang; Jiaqi Zou; Wenqing Li; Xuemei Xing; Xiaoxiao Gao; Jiao Lei; Fei Meng; Xin Wang; Yuzhang Zhu; Yu Cheng; et al. (Science Bulletin, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Challenges of quaternary ammonium antimicrobial agents: Mechanisms, resistance, persistence and impacts on the microecology - Jiaxin Zhang; Lei Cheng; Hao Li; Xi Chen; Lin Zhang; Tiantian Shan; Jiannan Wang; Ding Chen; Jiawei Shen; Xinxuan Zhou; Lichen Gou; Lixin Zhang; et al. (Science of The Total Environment, 2025)

Understanding the Impact of Hydroxyls on Synthesizing the Bimetallic Alloy Pt3Co on Al2O3 for CO-PROX - Jia Shen; Chen Chen; Lichuan Song; Liding Zhong; Kai Shan; Yanglong Guo; Wangcheng Zhan; Yun Guo; Haifeng Wang; Li Wang (Fuel, 2025)

Nitrogen addition alleviates the negative effects of reduction in precipitation on soil multifunctionality in a typical steppe - Yan Shen; Yonghong Luo; Lan Du; Ru Tian; Wenqian Shao; Jiatao Zhang; Na Li; Jinbao Zhang; Shan Wang; Mohsin Mahmood; Zhuwen Xu (Applied Soil Ecology, 2024)

Colorectal Cancer Complicated with Chronic Schistosoma Japonicum Infected: A Case Report - Shan Li; Yuling Shen; Ting Li; Yanqing Shi (Acta Parasitologica, 2024)

Constructing efficient Pd/Al2O3 catalyst for reverse water-gas shift via alkali-modification - Xi-Guang Wang; Lu-Yang Qiao; Li-Yuan Xu; Yun-Yun Zeng; Zhi-Shen Huang; Shan-Shan Zong; Jin-Xiang Wang; Zhang-Feng Zhou; Yuan-Gen Yao (Chemical Engineering Journal, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

ESR chronology of the Quaternary sedimentary sequence of the Shinaimiao borehole in Hebi City, Henan Province, China - Hao Ji; Zhong-shan Shen; Chun-Ru Liu; Xiong-Nan Huang; Xiao-Ping Yang; Chuan-Yi Wei; Xin-Xiu Li; Qing Zhou; Gong-Ming Yin (Quaternary Geochronology, 2024)

Assessing hydraulic fracturing feasibility in marine hydrate reservoirs: Impact of closure pressure and hydrate decomposition on fracture conductivity - Bing Li; Yifeng Shen; Youhong Sun; Yun Qi; Hengfeng Shan; Guobiao Zhang (Ocean Engineering, 2024)

Incorporation of hydroxyl groups and π-rich electron domains into g-C3N4 framework for boosted sacrificial agent-free photocatalytic H2O2 production - Yu Shen; Jinqi Shi; Yuhan Wang; Yuxing Shi; Pengnian Shan; Shunhong Zhang; Jianhua Hou; Feng Guo; Chunsheng Li; Weilong Shi (Chemical Engineering Journal, 2024)

Exploiting a tumor softening targeted bomb for mechanical gene therapy of chemoresistant Triple-Negative breast cancer - Yuting Shen; Xin Guan; Shaoyue Li; Xiaodong Hou; Jifeng Yu; Haohao Yin; Xuexia Shan; Xiaoxia Han; Lifan Wang; Boyang Zhou; Xiao Li; Liping Sun; et al. (Chemical Engineering Journal, 2024)

Photoelectron‐promoted metabolism of sulphate‐reducing microorganisms in substrate‐depleted environments - Chao Zhong; Anhuai Lu; Hailiang Dong; Shan Huang; Liang Shi; Yanan Shen; Yangjian Cheng; Yiran Dong; Xiangzhen Li; Jie Xu; Jinren Ni; Michael F. Hochella; et al. (Environmental Microbiology, 2024)
Sulphate‐reducing microorganisms, or SRMs, are crucial to organic decomposition, the sulphur cycle, and the formation of pyrite. Despite their low energy‐yielding metabolism and intense competition with other microorganisms, their ability to thrive in natural habitats often lacking sufficient substrates remains an enigma. This study delves into how Desulfovibrio desulfuricans G20, a representative SRM, utilizes photoelectrons from extracellular sphalerite (ZnS), a semiconducting mineral that often coexists with SRMs, for its metabolism and energy production. Batch experiments with sphalerite reveal that the initial rate and extent of sulphate reduction by G20 increased by 3.6 and 3.2 times respectively under light conditions compared to darkness, when lactate was not added. Analyses of microbial photoelectrochemical, transcriptomic, and metabolomic data suggest that in the absence of lactate, G20 extracts photoelectrons from extracellular sphalerite through cytochromes, nanowires, and electron shuttles. Genes encoding movement and biofilm formation are upregulated, suggesting that G20 might sense redox potential gradients and migrate towards sphalerite to acquire photoelectrons. This process enhances the intracellular electron transfer activity, sulphur metabolism, and ATP production of G20, which becomes dominant under conditions of carbon starvation and extends cell viability in such environments. This mechanism could be a vital strategy for SRMs to survive in energy‐limited environments and contribute to sulphur cycling.

Biotemplate synthesis of graphitic carbon-doped ZnO tube bundles rich in oxygen vacancies for dual-sensing of NO2/H2S at different temperatures - Zhao-Qi Cui; Rui Gao; Guo-Li Chen; Shi-Kai Shen; Zhao-Peng Deng; Ying-Ming Xu; Li-Hua Huo; Shan Gao (Chemical Engineering Journal, 2024)

Corrigendum to “Ionic-confining-assisted multiple-mode tunable light emitting of carbon nanodots” [Chem. Eng. J. 486 (2024) 150196] - Jing-Nan Hao; Zhong-Zheng Ding; Cheng-Long Shen; Guang-Song Zheng; Jia-Lu Liu; Ruo-Bing Li; Run-Wei Song; Kai-Kai Liu; Jin-Hao Zang; Lin Dong; Qing Lou; Chong-Xin Shan (Chemical Engineering Journal, 2024)

Metals/bisulfite system involved generation of 24-sulfonic-25-ene ginsenoside Rg1, a potential quality control marker for sulfur-fumigated ginseng - Hui Liu; Xiao-Qian Wu; Xiang-Ling Qin; Jin-Hao Zhu; Jin-Di Xu; Shan-Shan Zhou; Ming Kong; Hong Shen; Jie-Ge Huo; Song-Lin Li; He Zhu (Food Chemistry, 2024)

Injectable photocrosslinkable acellular cartilage matrix hydrogel loaded with exosomes for promoting growth plate injury repair - Xinxin Si; Quan Zhang; Bo Ning; Lei Qiang; Qiang Li; Yihao Liu; Minjie Fan; Jing Shan; Guanlu Shen; Zichen Lin; Pengfei Zheng (Chemical Engineering Journal, 2024)

Three new chromones from the whole plants of Chamaecrista rotundifolia and their anti-rotavirus activities - Pei-Song Yang; Xin-Yan He; Shan-Shan Li; De-Quan Huang; Si-Yu Shen; Xiao-Shan Liu; Yue-Yu Ma; Miao Dong; Min Zhou; Feng-Xian Yang; Yin-Ke Li (Natural Product Research, 2024)

Per- and polyfluoroalkyl substances and human health outcomes: An umbrella review of systematic reviews with meta-analyses of observational studies - Wei-Yi Xing; Jia-Nan Sun; Fang-Hua Liu; Li-Shen Shan; Jia-Li Yin; Yi-Zi Li; He-Li Xu; Yi-Fan Wei; Jia-Xin Liu; Wen-Rui Zheng; Ying-Ying Zhang; Xin-Jian Song; et al. (Journal of Hazardous Materials, 2024)

Preparation of green biodegradable lactic acid-based flame-retardant plasticizer for simultaneously enhancing flexibility, flame retardancy, and smoke-suppression of poly(lactic acid) - Boyou Hou; Xueying Shan; Haigang Yin; Jiandong Shen; Qiuze Wang; Jiaojiao Fang; Jinchun Li (Chemical Engineering Journal, 2024)

Enhanced stability of sodium anodes by amino-functioned macroporous two-dimensional nanodiamond coated polypropylene separators - Aijiao Li; Hui Wang; Xiaobing Liu; Weixia Shen; Chao Fang; Zhuangfei Zhang; Yuewen Zhang; Liangchao Chen; Qianqian Wang; Biao Wan; Ye Wang; Chongxin Shan (Chemical Engineering Journal, 2024)

Insights into atmospheric trace gases, aerosols, and transport processes at a high-altitude station (2623 m a.s.l.) in Northeast Asia - Ye Shan; Yujiao Zhu; Yanbi Qi; Yu Yang; Jiangshan Mu; Mingxuan Liu; Hongyong Li; Ji Zhang; Yanqiu Nie; Yuhong Liu; Min Zhao; Xin Zhang; et al. (Atmospheric Environment, 2024)

Material and microbial perspectives on understanding the role of biochar in mitigating ammonia inhibition during anaerobic digestion - Zhi-Jun Zhao; Xiao-Li Liu; Yi-Xuan Wang; Yan-Shan Wang; Jin-You Shen; Zhi-Cheng Pan; Yang Mu (Water Research, 2024)

Emergence of a clinical Salmonella enterica serovar 1,4,[5], 12: i:-isolate, ST3606, in China with susceptibility decrease to ceftazidime-avibactam carrying a novel blaCTX-M-261 variant and a blaNDM-5 - Jie Wei; Shimei Shen; Qinghuan Zhang; Jinping Lu; Shenglan Mao; Chunhong Zou; Hua Zhou; YeLin Wei; Xingyi Ou; Jinyu Huang; Deqiang Wang; Xiaobin Li; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2024)
Purpose The detection rate of Salmonella enterica serovar 1,4,[5], 12: i: - (S. 1,4,[5], 12: i: -) has increased as the most common serotype globally. A S . 1,4,[5], 12: i: - strain named ST3606 (sequence type 34), isolated from a fecal specimen of a child with acute diarrhea hospitalized in a tertiary hospital in China, was firstly reported to be resistant to carbapenem and ceftazidime-avibactam. The aim of this study was to characterize the whole-genome sequence of S. 1,4,[5], 12: i: - isolate, ST3606, and explore its antibiotic resistance genes and their genetic environments. Methods The genomic DNA of S. 1,4,[5], 12: i: - ST3606 was extracted and performed with single-molecule real-time sequencing. Resistance genes, plasmid replicon type, mobile elements, and multilocus sequence types (STs) of ST3606 were identified by ResFinder 3.2, PlasmidFinder, OriTfinder database, ISfinder database, and MLST 2.0, respectively. The conjugation experiment was utilized to evaluate the conjugation frequency of pST3606-2. Protein expression and enzyme kinetics experiments of CTX-M were performed to analyze hydrolytic activity of a novel CTX-M-261 enzyme toward several antibiotics. Results Single-molecule real-time sequencing revealed the coexistence of a 109-kb IncI1-Iα plasmid pST3606-1 and a 70.5-kb IncFII plasmid pST3606-2. The isolate carried resistance genes, including bla NDM-5 , sul1 , qacE , aadA2 , and dfrA12 in pST3606-1, bla TEM-1B , aac (3)- lld , and bla CTX-M-261 , a novel bla CTX-M-1 family member, in pST3606-2, and aac (6')- Iaa in chromosome. The bla CTX-M-261 was derived from bla CTX-M-55 by a single-nucleotide mutation 751G>A leading to amino acid substitution of Val for Met at position 251 (Val251Met), which conferred CTX-M increasing resistance to ceftazidime verified by antibiotics susceptibility testing of transconjugants carrying pST3606-2 and steady-state kinetic parameters of CTX-M-261. pST3606-1 is an IncI1-α incompatibility type that shares homology with plasmids of pC-F-164_A-OXA140, pE-T654-NDM-5, p_dm760b_NDM-5, and p_dmcr749c_NDM-5. The conjugation experiment demonstrated that pST3606-2 was successfully transferred to the Escherichia coli recipient C600 with four modules of OriTfinder. Conclusion Plasmid-mediated horizontal transfer plays an important role in bla NDM-5 and bla CTX-M-261 dissemination, which increases the threat to public health due to the resistance to most β-lactam antibiotics. This is the first report of bla CTX-M-261 and bla NDM-5 in S. 1,4,[5], 12: i: -. The work provides insights into the enzymatic function and demonstrates the ongoing evolution of CTX-M enzymes and confirms urgency to control resistance of S . 1,4,[5], 12: i: -.

Ionic-confining-assisted multiple-mode tunable light emitting of carbon nanodots - Jing-Nan Hao; Zhong-Zheng Ding; Cheng-Long Shen; Guang-Song Zheng; Jia-Lu Liu; Ruo-Bing Li; Run-Wei Song; Kai-Kai Liu; Jin-Hao Zang; Lin Dong; Qing Lou; Chong-Xin Shan (Chemical Engineering Journal, 2024)

Simultaneous regeneration of activated carbon and removal of adsorbed atrazine by ozonation process: From laboratory scale to pilot studies - Shan Liu; Zhonglin Chen; Yang Shen; Hao Chen; Zhenxin Li; Liming Cai; Hanbin Yang; Congshi Zhu; Jimin Shen; Jing Kang; Pengwei Yan (Water Research, 2024)

Per- and polyfluoroalkyl substances (PFASs) in Chinese surface water: Temporal trends and geographical distribution - Jie Wang; Cheng Shen; Jin Zhang; Guangyu Lou; Shengdao Shan; Yaqian Zhao; Yu Bon Man; Yuliang Li (Science of The Total Environment, 2024)

Microbial carbon and nitrogen limitation in Larix gmelinii forests along an altitudinal gradient: Evidence from ecoenzymatic stoichiometry and vector analysis - Chengfeng Shan; Mingwei Wang; Yuchun Yang; Fangyuan Shen; Li Ji; Lixue Yang (Applied Soil Ecology, 2024)

Associations between metal(loid) exposure with overweight and obesity and abdominal obesity in the general population: A cross-sectional study in China - Tianran Shen; Liling Zhong; Guiyuan Ji; Baolan Chen; Mengfan Liao; Lvrong Li; Huiming Huang; Jiajie Li; Yuan Wei; Shan Wu; Zihui Chen; Wenjun Ma; et al. (Chemosphere, 2024)

A study of typical plant growth changes in response to drainage water and salt in ditch wetland in arid area - Qian Wang; Shan Li; Liangjun Fei; Miao Wu; Runqiao Zheng; Youliang Peng; Fangyuan Shen (Science of The Total Environment, 2024)

Xylan cinnamoylation for reinforcing poly (butylene adipate-co-terephthalate): Molecule design and interaction optimization - Yanjun Chen; Jie Dai; Xin Shen; Junqiang Shan; Yulian Cao; Tianpeng Chen; Hanjie Ying; Chenjie Zhu; Ming Li (Carbohydrate Polymers, 2024)

Ultrasonic preparation of citral/hydroxypropyl-β-cyclodextrin inclusion complex: Application as a potential antifungal preservative in strawberry storage - Dan Shen; Xia Chang; Liling Zhou; Dandan Hao; Zhongxiang Fang; Yang Shan; Lvhong Huang; Gaoyang Li (Food Control, 2024)

Synthesis and evaluation of in vitro and in vivo anti -Toxoplasma gondii activity of tetraoxane-substituted ursolic acid derivatives - Ya-Lan Wang; Li-Li Jin; Xu Cheng; Wei-Feng Yan; Hao Deng; Qing-Kun Shen; Zhe-Shan Quan; Chun-Mei Jin; Chang-Hao Zhang (Natural Product Research, 2023)

Gene co-expression networks unravel the molecular responses of freshwater hydrophytes to combined stress of salinity and cadmium - Si-Qi Wang; Xiong-Li Zhou; Yan-Shan Jin; Erik Jeppesen; Liu Yang; Shi-Kang Shen (Chemosphere, 2023)

Precise classification and regional delineation of maturity groups in soybean cultivars across China - Wenwen Song; Luping Liu; Shi Sun; Tingting Wu; Haiyan Zeng; Shiyan Tian; Bincheng Sun; Wenbin Li; Lijun Liu; Shuming Wang; Han Xing; Xin’an Zhou; et al. (European Journal of Agronomy, 2023)

Formulating the Li sites of Li-CoOx composites for achieving high-efficiency oxidation removal of formaldehyde over the Ag/Li-CoOx catalyst under ambient conditions - Shi-Yu Zhang; Zhonghong Li; Xudong Shen; Jiajia Shan; Jingjing Zhan; Hao Zhou; Xianliang Yi; Hao-Yu Lian; Yang Liu (Environmental Research, 2023)

RIN enhances plant disease resistance via root exudate-mediated assembly of disease-suppressive rhizosphere microbiota - Keming Yang; Ruixin Fu; Haichao Feng; Gaofei Jiang; Omri Finkel; Tianyu Sun; Mingchun Liu; Baowen Huang; Shan Li; Xiaofang Wang; Tianjie Yang; Yikui Wang; et al. (Molecular Plant, 2023)

Prenatal polymetallic exposure and small for gestational age: A case-control study in Taiyuan, China - Zhitong Shen; Yue Lu; Zexin Song; Jinbo Li; Wangjun Li; Shan Li; Mengru Wang; Yongliang Feng; Suping Wang; Yawei Zhang; Weiwei Wu (Journal of Trace Elements in Medicine and Biology, 2023)

Efficient immobilization and detoxification of gaseous elemental mercury by nanoflower/rod WSe2/halloysite composite: Performance and mechanisms - Xuelei Duan; Yuan Li; Changxian Zhao; Yiwen Shen; Qi Guo; Zhihao Huang; Dexu Shan; Yue Gao; Kegang Zhang; Jianbo Shi; Jingfu Liu; Yongsheng Chen; et al. (Journal of Hazardous Materials, 2023)

Soil extracellular enzyme stoichiometry reveals the increased P limitation of microbial metabolism after the mixed cultivation of Korean pine and Manchurian walnut in Northeast China - Fangyuan Shen; Ning Liu; Chengfeng Shan; Li Ji; Mingwei Wang; Yujiao Wang; Lixue Yang (European Journal of Soil Biology, 2023)

Lobetyolin, a Q-marker isolated from Radix Platycodi, exerts protective effects on cisplatin-induced cytotoxicity in HEK293 cells - Yun-yi Hou; Si-min Qi; Jing Leng; Qiong Shen; Shan Tang; Jing-tian Zhang; Jun-nan Hu; Shuang Jiang; Wei Li (Journal of Natural Medicines, 2023)

Temperature effect on the axial behaviour of a pipeline buried in soft clay - Kuan-jun Wang; Li-zhong Wang; Yi Hong; Zhi-gang Shan; Hao-chen Liu; Kan-min Shen (Marine Georesources & Geotechnology, 2023)

Permeability damage and hydrate dissociation barrier caused by invaded fracturing fluid during hydrate reservoir stimulation - Yun Qi; Youhong Sun; Bing Li; Hengfeng Shan; Yifeng Shen; Guobiao Zhang (Gas Science and Engineering, 2023)

An online intelligent management method for wastewater treatment supported by coupling data-driven and mechanism models - Jian-Hui Wang; Du-Jiang Zhao; Wan-Shan Liao; Mohamed S. Mahmoud; Zhi-Wei Guo; Hui-Min Li; Xu Gao; Dong Feng; Long-Fei Shi; You-Peng Chen; Yu Shen (Journal of Water Process Engineering, 2023)

Expression of DDB1 is associated with subtypes of epithelial ovarian cancer and predicts clinical outcomes - Ying Shan; Banyun Mao; Ying Jin; Yan You; Yongxue Wang; Keng Shen; Lei Li (Tissue and Cell, 2023)

An effective tool for tracking steroids and their metabolites at the watershed level: Combining fugacity modeling and a chemical indicator - Ru Xu; Shan Liu; Hui Chen; Qin-Wei Hao; Yong-Xia Hu; Heng-Xiang Li; Lang Lin; Rui Hou; Bing Hong; Shen Yu; Xiang-Rong Xu (Environmental Pollution, 2023)

The risk factors associated with traumatic subdural effusion for patients with traumatic brain injury who did not undergo decompressive craniectomy - Xiangzhu Shen; Yafei Han; Haichang Li; Yu Dong; Dezhen Yang; Wei Xu; Shan Zhang (Acta Neurologica Belgica, 2023)

Stability Analysis of Wind Turbine Blades Based on Different Structural Models - Bin Wang; Ying Li; Shan Gao; Kanmin Shen; Shengxiao Zhao; Yu Yao; Zhilu Zhou; Zhenhong Hu; Xing Zheng (Journal of Marine Science and Engineering, 2023)
In order to better simulate the actual working conditions of wind turbines more realistically, this paper adopts the two-way fluid–structure coupling method to study the NREL 5 MW wind turbine, considering the blade coupling deformation and equivalent stress and strain distribution of the blades with different internal structures under different working conditions. The results show that the maximum equivalent stress and strain distribution of the beam–structure wind turbine blade was near the leading edge of the blade. The maximum equivalent stress and strain distribution of the shell structure wind turbine blade was near the leading edge of the blade root, and the dangerous area is obvious but smaller than that of the beam-type wind turbine. The coupled deformation of a wind turbine model with a shell structure blade with a web is significantly reduced, and the equivalent stress and strain distribution of the skin is similar to that of the shell structure, but the numerical value and the maximum equivalent stress distribution area are significantly smaller. From the comparison of the three, the shell structure blade with a web is the best.

Differential therapeutic activity of a cargo-free nanoparticle in eosinophilic and neutrophilic asthma mouse models - Xiali Liu; Huasheng Zhang; Huiqiang Ma; Jiameng Gong; Kaifeng Huang; Lu Wang; Yuting Ji; Liya Sun; Xiaoyu Wang; Li Li; Lei Shen; Shan-Yu Fung; et al. (Chemical Engineering Journal, 2023)

High-temperature polymer dielectrics with superior capacitive energy storage performance - Hongmei Qin; Jinhui Song; Man Liu; Yibo Zhang; Shiyu Qin; Hang Chen; Kangdi Shen; Shan Wang; Qi Li; Quanling Yang; Chuanxi Xiong (Chemical Engineering Journal, 2023)

Search for CP violation and measurement of branching fractions and decay asymmetry parameters for Λ c + → Λ h + and Λ c + → Σ 0 h + ( h = K , π ) - L.K. Li; W. Shan; K. Kinoshita; I. Adachi; H. Aihara; D.M. Asner; H. Atmacan; T. Aushev; V. Babu; S. Bahinipati; Sw. Banerjee; P. Behera; et al. (Science Bulletin, 2023)

MOF-implanted poly (acrylamide-co-acrylic acid)/chitosan organic hydrogel for uranium extraction from seawater - Yucheng Song; Hui Li; Tianhang Shan; Peipei Yang; Songwei Li; Zhong Liu; Chuntai Liu; Changyu Shen (Carbohydrate Polymers, 2023)

Developmental Exposure to Bisphenol a Degrades Auditory Cortical Processing in Rats - Binliang Tang; Kailin Li; Yuan Cheng; Guimin Zhang; Pengying An; Yutian Sun; Yue Fang; Hui Liu; Yang Shen; Yifan Zhang; Ye Shan; Étienne de Villers-Sidani; et al. (Neuroscience Bulletin, 2022)

Ancylostoma ceylanicum Infection in a Miniature Schnauzer Dog Breed - Xu-Hui Lin; Hai-Ming Cai; Zhuan-Qiang Yan; Shen-Quan Liao; Min-Na Lv; Cai-Yan Wu; Juan Li; Jun-Jing Hu; Wen-Wan Xiao; Jian-Fei Zhang; Nan-Shan Qi; Ming-Fei Sun (Acta Parasitologica, 2022)

Identification of microRNAs related with neural germ layer lineage-specific progenitors during reprogramming - Ruizhen Sun; Tiantian Gong; Hui Liu; Jingling Shen; Bin Wu; Qi Jiang; Qi Wang; Yue Zhang; Lian Duan; Jing Hu; Qiuming Li; Lei Lei; et al. (Journal of Molecular Histology, 2022)

A Deep Mesencephalic Nucleus Circuit Regulates Licking Behavior - Di Zheng; Jia-Yu Fu; Meng-Yu Tang; Xiao-Dan Yu; Yi Zhu; Chen-Jie Shen; Chun-Yue Li; Shi-Ze Xie; Shan Lin; Minmin Luo; Xiao-Ming Li (Neuroscience Bulletin, 2022)

Crocin Alleviates Intracerebral Hemorrhage–Induced Neuronal Ferroptosis by Facilitating Nrf2 Nuclear Translocation - Fei Wang; Wu-lin Li; Li-juan Shen; Ting-ting Jiang; Jian-jun Xia; Da-li You; Shan-you Hu; Li Wang; Xiao Wu (Neurotoxicity Research, 2022)

An integrated analysis of single-cell and bulk transcriptomics reveals EFNA1 as a novel prognostic biomarker for cervical cancer - Xiaopeng Shen; Meng Li; Yang Lei; Shan Lu; Sufen Wang; Zhongxian Liu; Chunguang Wang; Yun Zhao; Ao Wang; Chao Bi; Guoping Zhu (Human Cell, 2022)

Complete genomic sequence of Hibiscus latent Fort Pierce virus in a new host, Passilora edulis, in China - Lixue Xie; Fangluan Gao; Xuefeng Li; Xiaoyan Zhang; Shan Zheng; Lijie Zhang; Jianguo Shen; Tao Li (Journal of Plant Pathology, 2022)

Protective Effects of Zinc on Spinal Cord Injury - Shan Wen; Yuanlong Li; Xiaolei Shen; Zhe Wang; Kaihua Zhang; Jiawei Zhang; Xifan Mei (Journal of Molecular Neuroscience, 2021)

Promoting soil microbial-mediated suppressiveness against Fusarium wilt disease by the enrichment of specific fungal taxa via crop rotation - Xianfu Yuan; Beibei Wang; Shan Hong; Wu Xiong; Zongzhuan Shen; Yunze Ruan; Rong Li; Qirong Shen; Francisco Dini-Andreote (Biology and Fertility of Soils, 2021)

Genetic Architecture of Childhood Kidney and Urological Diseases in China - Ye Fang; Hua Shi; Tianchao Xiang; Jiaojiao Liu; Jialu Liu; Xiaoshan Tang; Xiaoyan Fang; Jing Chen; Yihui Zhai; Qian Shen; Guomin Li; Li Sun; et al. (Phenomics, 2021)
Kidney disease is manifested in a wide variety of phenotypes, many of which have an important hereditary component. To delineate the genotypic and phenotypic spectrum of pediatric nephropathy, a multicenter registration system is being implemented based on the Chinese Children Genetic Kidney Disease Database (CCGKDD). In this study, all the patients with kidney and urological diseases were recruited from 2014 to 2020. Genetic analysis was conducted using exome sequencing for families with multiple affected individuals with nephropathy or clinical suspicion of a genetic kidney disease owing to early-onset or extrarenal features. The genetic diagnosis was confirmed in 883 of 2256 (39.1%) patients from 23 provinces in China. Phenotypic profiles showed that the primary diagnosis included steroid-resistant nephrotic syndrome (SRNS, 23.5%), glomerulonephritis (GN, 32.2%), congenital anomalies of the kidney and urinary tract (CAKUT, 21.2%), cystic renal disease (3.9%), renal calcinosis/stone (3.6%), tubulopathy (9.7%), and chronic kidney disease of unknown etiology (CKDu, 5.8%). The pathogenic variants of 105 monogenetic disorders were identified. Ten distinct genomic disorders were identified as pathogenic copy number variants (CNVs) in 11 patients. The diagnostic yield differed by subgroups, and was highest in those with cystic renal disease (66.3%), followed by tubulopathy (58.4%), GN (57.7%), CKDu (43.5%), SRNS (29.2%), renal calcinosis /stone (29.3%) and CAKUT (8.6%). Reverse phenotyping permitted correct identification in 40 cases with clinical reassessment and unexpected genetic conditions. We present the results of the largest cohort of children with kidney disease in China where diagnostic exome sequencing was performed. Our data demonstrate the utility of family-based exome sequencing, and indicate that the combined analysis of genotype and phenotype based on the national patient registry is pivotal to the genetic diagnosis of kidney disease.

Vibrio marinisediminis sp. nov., Isolated from Marine Sediment - Huilin Zhao; Jiangfan Shan; Taojie Wang; Yue Tian; Yingjian Shen; Zongjun Du; Boqing Li; Xiaofei Ji (Current Microbiology, 2021)

Inland fisheries development versus aquatic biodiversity conservation in China and its global implications - Hui Zhang; Jinming Wu; Harry Gorfine; Xiujuan Shan; Li Shen; Haile Yang; Hao Du; Junyi Li; Chengyou Wang; Qiong Zhou; Zhigang Liu; Myounghee Kang; et al. (Reviews in Fish Biology and Fisheries, 2020)

Metabolites from symbiotic bacteria of entomopathogenic nematodes have antimicrobial effects against Pythium myriotylum - Shaojie Shan; Haikun Ma; Yang Li; Cuiqing Huang; Xinghui Gu; Zhensheng Jiang; Bingjiao Sun; Chaoying Chen; Xianqin Wei; Guangshuang Shen; David Shapiro-Ilan; Weibin Ruan (European Journal of Plant Pathology, 2020)

Prenatal di-(2-ethylhexyl) phthalate maternal exposure impairs the spatial memory of adult mouse offspring in a phase- and gender-dependent manner - Ling-Li Zhao; Ru Shen; Cong-Cong Sun; Shan-Yu Zhang; Bo Wang; Mei-Fang Sun; De-Xiang Xu (Environmental Science and Pollution Research, 2020)

Characterization of Pingliang xiaoheidou (ZDD 11047), a soybean variety with resistance to soybean cyst nematode Heterodera glycines - Wei Guo; Jing S. Chen; Feng Zhang; Ze Y. Li; Hai F. Chen; Chan J. Zhang; Li M. Chen; Song L. Yuan; Rong Li; Dong Cao; Qing N. Hao; Shui L. Chen; et al. (Plant Molecular Biology, 2020)

Physiological and proteomic responses of mangrove plant Avicennia marina seedlings to simulated periodical inundation - Huan Li; Zan Li; Zhi-Jun Shen; Mei-Rong Luo; Yi-Ling Liu; Ming-Yue Wei; Wen-Hua Wang; Ying-Ying Qin; Chang-Hao Gao; Ke-Ke Li; Qian-Su Ding; Shan Zhang; et al. (Plant and Soil, 2020)

Giant Submarine Landslide in the South China Sea: Evidence, Causes, and Implications - Chaoqi Zhu; Sheng Cheng; Qingping Li; Hongxian Shan; Jing’an Lu; Zhicong Shen; Xiaolei Liu; Yonggang Jia (Journal of Marine Science and Engineering, 2019)
Submarine landslides can be tremendous in scale. They are one of the most important processes for global sediment fluxes and tsunami generation. However, studies of prodigious submarine landslides remain insufficient. In this review paper, we compile, summarize, and reanalyze the results of previous studies. Based on this reanalysis, we discover the giant Baiyun–Liwan submarine slide in the Pearl River Mouth Basin, South China Sea. We describe three concurrent pieces of evidence from ~23 Ma to 24 Ma, the Oligocene–Miocene boundary, for this landslide: the shoreward shift of the shelf break in the Baiyun Sag, the slump deposition to the southeast, and the abrupt decrease in the accumulation rate on the lower continental slope. This landslide extends for over 250 km, and the total affected area of the slide is up to ~35,000–40,000 km2. The scale of the landslide is similar to that of the Storegga slide, which has long been considered to be the largest landslide on earth. We suggest that strike–slip movement along the Red River Fault and ridge jump of the South China Sea caused the coeval Baiyun–Liwan submarine slide. The identification of the giant landslide will promote the understanding of not only its associated geohazards but also the steep rise of the Himalayan orogeny and marine engineering. More attention needs to be paid to areas with repeated submarine landslides and offshore installations.

A case control study on the prevalence of enterovirus in children samples and its association with diarrhea - Xin-xin Shen; Fang-zhou Qiu; Gui-xia Li; Meng-chuan Zhao; Ji Wang; Chen Chen; Li Zhao; Ju-Ju Qi; Hong Liu; Yi Zhang; Xiao-zhou He; Le Wang; et al. (Archives of Virology, 2019)

Volumetric comparison of hippocampal subfields extracted from 4-minute accelerated vs. 8-minute high-resolution T2-weighted 3T MRI scans - Shan Cong; Shannon L. Risacher; John D. West; Yu-Chien Wu; Liana G. Apostolova; Eileen Tallman; Maher Rizkalla; Paul Salama; Andrew J. Saykin; Li Shen (Brain Imaging and Behavior, 2018)

Streptomyces lutosisoli sp. nov., a novel actinomycete isolated from muddy soil - Yue Shen; Tianyu Sun; Shanwen Jiang; Shan Mu; Dongmei Li; Xiaowei Guo; Jianli Zhang; Junwei Zhao; Wensheng Xiang (Antonie van Leeuwenhoek, 2018)

Neutrophil-to-Lymphocyte Ratio Is an Independent Predictor of 30-Day Mortality of Intracerebral Hemorrhage Patients: a Validation Cohort Study - Fei Wang; Li Wang; Ting-ting Jiang; Jian-jun Xia; Feng Xu; Li-juan Shen; Wen-hui Kang; Yong Ding; Li-xia Mei; Xue-feng Ju; Shan-you Hu; Xiao Wu (Neurotoxicity Research, 2018)

Localization of Maize Critical N Curve and Estimation of NNI by Chlorophyll - Xiao-Gui Liang; Zuo-Lin Zhang; Li-Li Zhou; Si Shen; Zhen Gao; Li Zhang; Shan Lin; Yu-Qiang Pan; Shun-Li Zhou (International Journal of Plant Production, 2018)

Combination of High-Sensitivity C-Reactive Protein and Homocysteine Predicts the Post-Stroke Depression in Patients with Ischemic Stroke - Li-Shan Cheng; Wen-Jun Tu; Yuan Shen; Li-Jun Zhang; Kangxiang Ji (Molecular Neurobiology, 2018)

Comparisons of Evaluation Factors and Application Effects of the New [BQ]GSI System with International Rock Mass Classification Systems - Shen Yan-jun; Yan Rui-xin; Yang Geng-she; Xu Guang-li; Wang Shan-yong (Geotechnical and Geological Engineering, 2017)

An overlooked nitrogen loss linked to anaerobic ammonium oxidation in estuarine sediments in China - Xiao-Ru Yang; Bo-Sen Weng; Hu Li; Christopher W. Marshall; Hong Li; Yong-Shan Chen; Shen Yu; Gui-Bing Zhu; Yong-Guan Zhu (Journal of Soils and Sediments, 2017)

DAPK1 Signaling Pathways in Stroke: from Mechanisms to Therapies - Shan Wang; Xiangde Shi; Hao Li; Pei Pang; Lei Pei; Huiyong Shen; Youming Lu (Molecular Neurobiology, 2017)

MCP1 triggers monocyte dysfunctions during abnormal osteogenic differentiation of mesenchymal stem cells in ankylosing spondylitis - Zhongyu Xie; Peng Wang; Jinteng Li; Yuxi Li; Shan Wang; Xiaohua Wu; Suhe Sun; Shuizhong Cen; Hongjun Su; Wen Deng; Zhenhua Liu; Yi Ouyang; et al. (Journal of Molecular Medicine, 2017)

Adoptive therapy with CAR redirected T cells for hematological malignancies - Shiqi Li; Zhi Yang; Junjie Shen; Juanjuan Shan; Cheng Qian (Science China Life Sciences, 2016)

Effects of sialidase NEU1 siRNA on proliferation, apoptosis, and invasion in human ovarian cancer - Li-rong Ren; Li-ping Zhang; Shu-ying Huang; Yuan-fang Zhu; Wen-juan Li; Shan-yu Fang; Li Shen; Yan-ling Gao (Molecular and Cellular Biochemistry, 2016)

Identification of SNPs in NPY and LEP and the association with food habit domestication traits in mandarin fish - JIAN SUN; SHAN HE; XU-FANG LIANG; LING LI; ZHENGYONG WEN; TAO ZHU; DAN SHEN (Journal of Genetics, 2015)

Little effect of natural noise on high-frequency hearing in frogs, Odorrana tormota - Jing Liu; Han Yang; Guang-Lei Hu; Shan Li; Zhi-Min Xu; Zhi Qi; Jun-Xian Shen (Journal of Comparative Physiology A, 2015)

Loss of Egr-1 sensitizes pancreatic β-cells to palmitate-induced ER stress and apoptosis - Mun-Wai Cheong; Li-Hua Kuo; Yi-Ning Cheng; Pei-Jane Tsai; Li-Chun Ho; Haw-Chih Tai; Wen-Tai Chiu; Shun-Hua Chen; Pei-Jung Lu; Yan-Shen Shan; Lee-Ming Chuang; Yau-Sheng Tsai (Journal of Molecular Medicine, 2015)

Protein prenylation and human diseases: a balance of protein farnesylation and geranylgeranylation - Na Xu; Ning Shen; XiuXing Wang; Shan Jiang; Bin Xue; ChaoJun Li (Science China Life Sciences, 2015)

Identification of Sugarcane White Leaf Phytoplasma in Fields and Quaratine Sugarcane Samples in Yunnan Province, China - Xiao-Yan Wang; Wen-Feng Li; Ying-Kun Huang; Rong-Yue Zhang; Hong-Li Shan; Zhi-Ming Luo; Jiong Yin; Ke Shen (Sugar Tech, 2015)

Model Drug as Pore Former for Controlled Release of Water-Soluble Metoprolol Succinate from Ethylcellulose-Coated Pellets Without Lag Phase: Opportunities and Challenges - Yuli Wang; Jingjing Dai; Xinyi Chang; Meiyan Yang; Ruifang Shen; Li Shan; Yong Qian; Chunsheng Gao (AAPS PharmSciTech, 2015)

The prevalence of heifer mastitis and its associated risk factors in Huanggang, Central China - Feng Li Yang; Chen Shen; Bao Xiang He; Yu Ying Yang; Da Chun Gong; Xiao Shan Li (Tropical Animal Health and Production, 2015)

Accumulation of FLT3+ CD11c+ dendritic cells in psoriatic lesions and the anti-psoriatic effect of a selective FLT3 inhibitor - Heng-Xiu Yan; Wei-Wei Li; Yan Zhang; Xia-Wei Wei; Li-Xin Fu; Guo-Bo Shen; Tao Yin; Xiu-Ying Li; Hua-Shan Shi; Yang Wan; Qing-Yin Zhang; Jiong Li; et al. (Immunologic Research, 2014)

Monitoring of urban heat island in Shanghai, China, from 1981 to 2010 with satellite data - Cheng-fan Li; Di Shen; Jiang-shan Dong; Jing-yuan Yin; Jun-juan Zhao; Dan Xue (Arabian Journal of Geosciences, 2014)

Biodegradation of 1,4-Dioxane by a Novel Strain and Its Biodegradation Pathway - Huanlin Huang; Dongsheng Shen; Na Li; Dan Shan; Jiali Shentu; YuYang Zhou (Water, Air, & Soil Pollution, 2014)

A comparative study of intensive Litopenaeus vannamei culture on four bottom substrates without water change - Hongwei Shan; Li Zhang; Lei Gao; Yuepeng Su; Weiyang Bao; Shen Ma (Journal of Ocean University of China, 2014)

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

Screening wheat genotypes for resistance to black point and the effects of diseased kernels on seed germination - Qiao-Yun Li; Zhao Qin; Yu-Mei Jiang; Chun-Cai Shen; Zong-Biao Duan; Ji-Shan Niu (Journal of Plant Diseases and Protection, 2014)

Functional study on the mutations in the silkworm (Bombyx mori) acetylcholinesterase type 1 gene (ace1) and its recombinant proteins - Ju-mei Wang; Bin-bin Wang; Yi Xie; Shan-shan Sun; Zhi-ya Gu; Lie Ma; Fan-chi Li; Yi-fan Zhao; Bin Yang; Wei-de Shen; Bing Li (Molecular Biology Reports, 2014)

Genome-wide association study identifies HMGN3 locus for spine bone size variation in Chinese - Shu-Feng Lei; Hui Shen; Tie-Lin Yang; Yan Guo; Shan-Shan Dong; Xiang-Hong Xu; Fei-Yan Deng; Qing Tian; Yong-Jun Liu; Yao-Zhong Liu; Jian Li; Hong-Wen Deng (Human Genetics, 2012)

Genomic organization and recombination analysis of human norovirus identified from China - Quan Shen; Wen Zhang; Shixing Yang; Yan Chen; Tongling Shan; Li Cui; Xiuguo Hua (Molecular Biology Reports, 2012)

Effects of salvianolic acid B on proliferation, neurite outgrowth and differentiation of neural stem cells derived from the cerebral cortex of embryonic mice - GuoQing Guo; Bin Li; YuanYuan Wang; AiJing Shan; WeiZai Shen; Lin Yuan; ShiZhen Zhong (Science China Life Sciences, 2010)

Sequence analysis of rDNA intergenic spacer (IGS) of Porphyra haitanensis - Yanyan Li; Songdong Shen; Lihong He; Pu Xu; Shan Lu (Journal of Applied Phycology, 2010)

Molecular detection and prevalence of porcine caliciviruses in eastern China from 2008 to 2009 - Quan Shen; Wen Zhang; Shixing Yang; Yan Chen; Huibo Ning; Tongling Shan; Junfeng Liu; Zhibiao Yang; Li Cui; Jianguo Zhu; Xiuguo Hua (Archives of Virology, 2009)

Expression of EGFP driven by BmNPV orf4 promoter, a novel immediate early promoter - Wu-Jie Su; Bing Li; Wei-De Shen; Yan Wu; Shan-Ying Zhu; Ying Sun; Wen-Bing Wang (Biologia, 2009)

Altered gene expression of NIDD in dorsal root ganglia and spinal cord of rats with neuropathic or inflammatory pain - Meng-Ling Chen; Chun Cheng; Qing-Shan Lv; Zhi-Qin Guo; Ying Gao; Shang-Feng Gao; Xin Li; Shu-Qiong Niu; Shu-Xian Shi; Ai-Guo Shen (Journal of Molecular Histology, 2008)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)